(untitled) (Journal of Fiber Bioengineering and Informatics, 2020)
Six phase change materials (PCMs) were prepared by blending polyethylene glycol (PEG) with laponite powders (LP) at different ratios (PEG:LP, 100:0, 97:3, 96:4, 91:9, 88:12 and 85:15) under 100◦C firstly. A multi-layer composite consisting of a PCM loaded layer, a nano barrier layer and a protective layer was used to hold PEG/LP PCMs. SEM was used to observe the morphological structure of multi-layer composites containing PEG/LP composites. DSC revealed the melting temperature, the cooling temperature and the enthalpy of PEG and laponite as PCM. The thermal insulation of all the composites containing PEG/LP was evaluated under 78◦C. The results gave that the multi-layer composite containing PCM was obtained and a better adhesion of between the PCM loaded layer, the nano barrier layer and the protective layer was found. LP functionalized as a nucleating agent to accelerate the crystallization of PEG and 15wt% LP in PCM resulted in a disordered PEG molecular. The composites with more laponite had the higher thermal insulation and highest value reached 0.25.